A Matter of Time: Enacting the Exclusion of Onshore Refugee Applicants through the Reform and Acceleration of Refugee Determination Processes - Vogl, Anthea (Oñati Socio-Legal Series, 2016)
State-based processes for determining refugee claims are crucial sites of inclusion or exclusion for onshore refugee applicants. This paper argues that cultures of disbelief and exclusion towards onshore refugee applicants are increasingly being enacted indirectly, via procedural reforms to Refugee Status Determination (RSD), which limit the ability of applicants to establish and articulate their claims. Focusing on Australia and Canada, this paper tracks the acceleration and truncation of RSD procedures, which first reflect and then frequently achieve the exclusion of onshore applicants. Two sets of reforms in particular have profoundly limited the terms on which applicants may present their claims. In Canada, this occurred as the result of a major overhaul of RSD that took place in December 2012. In Australia, the policy of ‘enhanced screening’ of applicants achieves the immediate screening-out of certain claims from the Australian determination system. Alongside analysing these reforms as a means of exclusion, this paper argues that the new procedures most disadvantage applicants making claims on the basis of gender-related persecution.